Etika Pelayanan Publik Di Kantor Kecamatan Enrekang Kabupaten Enrekang - Hendrawan TPP, Moch Edy; Wahid, Nur; Hawing, Hardianto (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
Providing services cannot be separated from service ethics which of course has an impact on public satisfaction with the services provided at the Enrekang District Office. This research certainly discusses public service ethics which are summarized in four indicators, namely Equality, Quity, Loyalty and Responsibility. The research results showed that the four indicators were still far from what was expected, where the four indicators were not included in a Standard Operating Procedure. The absence of Standard Operating Procedures is a benchmark for the services provided by the Enrekang District Office. So in this case, presenting Standard Operating Procedures is intended as a guideline in providing public services which of course cannot be separated from the four indicators of public service ethics discussed. Therefore, the recommendation from researchers is of course that the establishment of Standard Operating Procedures must be implemented at the Enrekang District Office as an effort to realize excellent public services.